Beyond enrolments: the determinants of primary-school attendance in Melanesia. Issue 4 (1st October 2016) - Posso, Alberto; Feeny, Simon
ABSTRACT: The second millennium development goal (MDG) is to achieve universal primary education and while developing countries have made good progress on primary-school enrolment rates, school attendance remains low. This paper addresses the determinants of school attendance using unique household survey data for two Melanesian economies rarely reported in the international literature: Solomon Islands and Vanuatu. There is a high degree of heterogeneity in the results across both gender and location. The main findings are that as children get older, they are less likely to attend school as are children that work either inside or outside the home. School fees act as a major deterrent for sending children to school, even though governments and international donors have taken significant steps to make primary education free. Finally, community programs that aim at increasing school attendance have been successful, particularly for girls and children in remote areas. A number of policy implications are provided.